Implementation of Information Technology Algorithms Based on ICT Media to Make Teachers Have 21st Century Skills - Yolviansyah, Fauziah; Amin, Nor Fadila; Retutas, Mildin; Tuan, Nguyen Anh; Peiling, Liu (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to improve technological literacy and 21st century skills of teachers through the implementation of algorithms based on ICT media, relevant to the demands of the Industrial Revolution 5.0 era. Methodology: The research method uses an experimental approach with a pretest-posttest design and data collection through questionnaires and observations. Training was given to 30 high school teachers using algorithmic technology and ICT media. The data analysis used was parametric statistics using the t-test.. Main Findings: The results of the study showed a significant increase in technological literacy and 21st century skills, with an average increase of 26.9%, especially in the ICT Media aspect. Novelty/Originality of this study: The novelty of this research lies in the futuristic algorithmic integration in ICT media for learning, which provides an innovative solution for teacher competency development. This finding is expected to be a guide in designing technology-based training programs for adaptive and innovative education.